2021
DOI: 10.1021/acs.macromol.1c01141
|View full text |Cite
|
Sign up to set email alerts
|

The Brill Transition in Long-Chain Aliphatic Polyamide 1012: The Role of Hydrogen-Bonding Organization

Abstract: The effect of hydrogen-bond (H-bond) organization, evaluated by the crystal perfection index (CPI), on the Brill transition of long-chain polyamide 1012 upon heating was investigated with variable-temperature wide-angle X-ray diffraction (WAXD), small-angle X-ray scattering (SAXS), and Fourier transform infrared spectroscopy (FTIR). A sufficiently high cooling rate was required to prepare samples with randomly distributed H-bonds (i.e., a low CPI) because this inhibits the reorganization of the 2-D hydrogen sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 58 publications
5
79
0
Order By: Relevance
“…As the more perfect and bigger the crystals are, the T B will be found in a higher position. However, recently, it has been pointed out that the amorphous phase may also play a key role, as well as the hydrogen bond organization …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the more perfect and bigger the crystals are, the T B will be found in a higher position. However, recently, it has been pointed out that the amorphous phase may also play a key role, as well as the hydrogen bond organization …”
Section: Introductionmentioning
confidence: 99%
“…The Brill transition has been widely studied in the polyamide family, ,, and recently, a Brill-like transition has been reported for poly­(octamethylene carbonate) (PC8) and poly­(hexamethylene dithiocarbonate) (PC6-D) . In PC8, Zhao et al reported the convergence, upon heating, of the d 110 = 0.43 nm and d 200 = 0.38 nm, observed at low temperatures (in the denoted α phase), into a single d -spacing at 0.41 nm at ∼42 °C (in the denoted β phase).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAs can undergo crystal transition behavior under the applied thermal or elongation fields, such as the reversible transition of PA66 from a triclinic phase to a pseudohexagonal phase upon heating (known as the Brill transition), which was first reported by Brill in 1942. 15 Numerous investigations into Brill transition under external fields have been reported for various PAs, 1,2,16 for example, PA6, 17−19 PA1010, 20 PA1012, 8,21,22 their composites, 23−26 and copolymers. 27−29 As a typical AABB-type even−even long-chain PA (LCPA), the most thermodynamically stable crystal phase in triclinic symmetry of PA1012 is denoted the α-phase, which is featured by the H-bonds all arranged along the a-axis of its unit cell to establish the hydrogen bonding sheets (H-sheets) held together by van der Waals interaction in a well-defined progressive packing along the b-axis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been demonstrated that T B is highly dependent on the crystallization conditions, 40 which affects the characteristics such as the thickness distribution of lamellae 20 and the H-bond organization. 8 In addition, blending with fillers 24,25,40,41 and chemical modification by inserting the comonomers 29,42−44 in the main chain are two effective ways to control T B . Liu et al found that the T B of PA66 was decreased by blending with silicate and attributed it to the strong interaction between PA66 chains and surfaces of silicate layers.…”
Section: ■ Introductionmentioning
confidence: 99%